STUDI EKSPLORATIF: KEMAMPUAN GURU SLB MENGEMBANGKAN ASESMEN PEMBELAJARAN BERBASIS KEARIFAN LOKAL DI PROVINSI BALI - I Wayan Widana (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
The government's policy to develop a Pancasila student profile for students is the focus of developing the quality of education in Indonesia. This study aims to analyze the ability of special school teachers to develop learning assessments based on local wisdom, as one of the supporters of developing Pancasila student profiles for students with special needs. The research population is teachers of public and private special schools in the province of Bali. The research method uses a mixed methods approach. Qualitative data were collected using observation sheets, document studies, and interviews. Qualitative research informants were determined by purposive sampling technique. Meanwhile, quantitative data was collected using a questionnaire instrument which was circulated online. Sample selection using random sampling technique. The number of special school teachers who responded was 49 people. The research data were analyzed using mixed methods. The results showed that quantitatively: (a) the responsibility of extraordinary school teachers to carry out tasks (X1) with an average score of 59.63 (Good), (b) extraordinary school teachers' understanding of the concept of learning evaluation (X2) with an average score -average 75.53 (Enough), (c) extraordinary school teacher's understanding of local wisdom (X3) with an average score of 71.27 (Good), and (d) extraordinary school teacher's ability to develop learning instruments based on local wisdom with an average score of 56.31 (Enough). In conclusion, special school teachers in Bali Province need to be motivated and facilitated to improve their ability to develop learning assessments based on local wisdom.